The performance of double-clad ytterbium-doped fiber laser with different pumping wavelengths - Harun, Sulaiman Wadi; Moghaddam, M.R.A.; Dimyati, Kaharudin; Ahmad, Harith (IOP Publishing, 2009)
The effect of pumping wavelengths on the performance of double-clad Ytterbium-doped fiber laser (YDFL) is experimentally demonstrated. The YDFL is constructed using a fiber Bragg grating as wavelength selective filter in a linear cavity resonator. The YDFL operates at wavelength of 1064.4 nm with a bandwidth of 0.2 nm and signal to noise ratio of more than 30 dB. The efficiency of the YDFL is observed to depend on the absorption cross section spectrum of the YDF. The slope efficiencies of the YDFL are obtained at 60.4% and 67.5% for the pumping wavelengths of 937 nm and 967 nm, respectively. The threshold power to achieve lasing is approximately 0.5 W for both pumping wavelengths.